Expression dynamics of innate immunity in influenza virus-infected swine - Montoya, Maria; Foni, Emanuela; Solórzano, Alicia; Razzuoli, Elisabetta; Baratelli, Massimiliano; Bilato, Dania; Córdoba, Lorena; del Burgo, Maria Angeles Martín; Martínez Martínez, Jorge; Martinez-Orellana, Pamela; Chiapponi, Chiara; Perlin, David S.; et al. (Frontiers in Veterinary Science, 2017)
We would like to thank Dr. Jaime Maldonado and HIPRA, Spain for the A/swine/Spain/54008/2004 (H3N2) influenza virus; Dr. Dubovi and Cornell University for the A/Canine/NY/105447/08 (H3N8) influenza virus; Dr. Chambers and University of Kentucky for the A/Equine/OH/1/03 (H3N8) influenza virus; and Dr. Hon Ip and the US Geological Survey National Wildlife Health Center for the A/American black duck/Maine/44411-532/2008 (H3N8) and the A/Harbour Seal/New Hampshire/179629/2011 (H3N8) influenza viruses. The authors thank Sergio López, David Solanes and Francisco X. Abad for their help during the experimental infections as well as the personnel in Cat3 laboratories and animal house. The authors also wish to thank Dr. I. L. Archetti (IZSLER, Brescia, Italy) for the invaluable help in measuring some clinical immunology parameters, Dr. L. Fraile (UdL, Spain) for assistance in statistical analysis, Dr. J. Domínguez (INIA, Spain) for porcine antibodies, Dr. M. Gennari and Dr. M. Giunta (S.S. Genova, IZSPLV, Italy) for assistance in real-time PCR analyses. The skillful technical assistance of Mrs. C. Mantovani (IZSLER, Brescia, Italy) is also gratefully acknowledged. The research leading to these results has received funding from: the European Community's Seventh Framework Programme (FP7, 2007-2013), Research Infrastructures action, under the grant agreement No. FP7-228393 (NADIR project), and from the project AGL2010-22200-C02-01 of Spanish Ministry of Science and Innovation. Geological Survey National Wildlife Health Center/[u'duck/Maine/44411-532/2008', u'H3N8'] The current circulating swine influenza virus (IV) subtypes in Europe (H1N1, H1N2, and H3N2) are associated with clinical outbreaks of disease. However, we showed that pigs could be susceptible to other IV strains that are able to cross the species barrier. In this work, we extended our investigations into whether different IV strains able to cross the species barrier might give rise to different innate immune responses that could be associated with ...